Impact of Parental Adverse Childhood Experiences on Offspring Development in Early Head Start: Parental Adversity and Offspring Development - Antonela Miccoli; Joanne Song; Magdalena Romanowicz; Flora Howie; Sandy Simar; Brian A. Lynch (SAGE Publishing, 2022)
Adverse childhood experiences (ACEs) are potentially traumatic events that can cause lifelong suffering, with 1 out of 2 children in the United States experiencing at least 1 ACEs. The intergenerational effect of ACEs has been described, but there's still paucity of knowledge of its impact on child development and behavior in children enrolled in Early Head Start (EHS) home visiting programs. A retrospective observational study was performed with 71 parents and 92 children participating in the EHS Home Visiting Program in Olmsted County from 2014 to 2019. Parents reported their own ACEs using a 10-item questionnaire. Children's social-emotional status was evaluated with Devereux Early Childhood Assessment Second Edition (DECA) and development was evaluated using the Brigance Early Childhood Screens III. Referrals of children by EHS staff to community agencies were recorded. The association between parental ACEs score, developmental outcomes and referrals was analyzed. Parental ACEs score of 4 or more was associated with failing at least 1 domain on the Brigance screen ( P  = .02) especially adaptive/cognitive domain ( P  = .05), and increased risk of referral to community resources ( P  < .001). However, there was no association between ACEs scores and failing DECA screens. We identified an intergenerational association between parental exposure to ACEs and risk for childhood developmental delay and referrals to community services. Parental adverse childhood experiences (ACEs) have intergenerational effects on offspring. In our study, parental ACEs are associated with offspring developmental delays and referral to community resources. Screening for parental adverse childhood experiences, a key social determinant of health, is imperative and should be incorporated into primary care and early childhood settings to identify children at risk for developmental delay.